Enriched clonal hematopoiesis in seniors with dietary vitamin C inadequacy. (December 2021) - Chen, Jiaqi; Nie, Daijing; Wang, Xinyu; Wang, Lei; Wang, Fang; Zhang, Yang; Chen, Xue; Cao, Panxiang; Li, Minghua; Ma, Xiaoli; Yu, Tongtong; Zhou, Xiaosu; et al.
Summary: Background: The anti-cancer effect of vitamin C (VC) has long been speculated, but studies yielded inconsistency. Recent studies reported that supraphysiological concentration of VC have therapeutic or prevention effects for myeloid malignancies with certain mutation signatures. There was a notable proportion of DAT (i.e., DNMT3A, ASXL1, and TET2 ) and dozens of other genes that mutate in age-related clonal hematopoiesis (ARCH). Methods and results: Through analyzing the plasma VC concentration and mutations of 21 genes in 215 senior volunteers, we revealed that ARCH is significantly associated with dietary plasma VC concentrations, especially TET2 mutations and non-DAT mutations. Conclusion: This study firstly disclosed the significant association between VC inadequacy and ARCH in the senior population. It provides evidence that physiological VC concentration has ARCH prevention effect. It will illuminate future explorations on the oral VC supplement in maintaining sound hematopoiesis, reversal ARCH, adjuvant therapy for myeloid malignancies, and prevention of other ARCH related comorbidities.